Exploring the Impact of Lifelong Education Theory on Curriculum and Teaching Reform in Chinese Primary and Secondary Schools: Insights for Sports Education and Psychological Development - Qi Jiang; Junyang Zhang; Zimu Yang; Chuanlan Tang; Lu Wang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The theory of lifelong education underscores the idea that education should extend beyond traditional educational stages, encompassing the entire lifespan from cradle to grave. This approach advocates for education systems to be fully accessible to all members of society, emphasizing the actual needs of learners and fostering the development of lifelong learning attitudes and abilities. Lifelong education theory not only provides a robust theoretical foundation but also significantly influences curriculum and teaching reforms in primary and secondary schools in China. This study explores the impact of lifelong education theory on the objectives, curriculum design, teaching content, and pedagogical methods in China's education system, particularly in the context of sports education. By aligning educational reforms with the principles of lifelong learning, schools can foster holistic student development, promoting not only academic success but also psychological resilience, physical fitness, and social skills. The integration of lifelong education principles into sports curricula can further support the development of healthy habits, teamwork, and a positive mindset, ensuring that education contributes to both cognitive and physical well being throughout life.